“WOMEN SOCIAL ENTREPRENEURSHIP IN ACTION’’ A CASE STUDY OF WOMEN SOCIAL ENTREPRENEURSHIP INITIATIVES IN TAMIL NADU (INDIA) - Natrajan, Rebecca (PEOPLE: International Journal of Social Sciences, 2019)
Entrepreneurs are not homogeneous and their initiatives determine the social and economic development of a nation. They are able to position themselves successfully in the local and global market. Many scholars and academicians addressed the functions of entrepreneurs especially women commercial entrepreneurs and their involvement to improve the society. However, there is an urgent need to create awareness among women about social entrepreneurship initiatives, due to an increasingly number of problems that women have been facing in the society. This paper aims to discuss the hindering factors and the support system that is required to promote women social entrepreneurs. This research paper focussed on young and small pioneer organisations. The researcher used case study analysis based on semi-structured interviews with women social entrepreneurs in Tamil Nadu (India) being mainly young and small pioneer organizations. The researcher provided some valuable suggestions to increase the number of women social entrepreneurship initiatives along with the scope for further research.